3D Printed Helical Soft Pneumatic Actuators - Hu, Weiping; Li, Weihua; Alici, Gursel (2018 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (AIM), 2018)
Nature abounds with complex, three-dimensional shapes, and helices which are some of the most common structures in nature. This article describes a new soft pneumatic actuator that generates bending and twisting motions. The actuator consists of several angled chambers arranged in a line that can be actuated simultaneously using one power source (air pressure). The bending and twisting trajectory of the actuator has been characterized by changing the length of the actuator, the number of chambers, and the angle of chambers using the finite element analysis (FEA). The 3D printing method of fused filament fabrication (FFF) type was employed to directly manufacture the thin-walled, airtight, and low cost helical actuators, without requiring any post-manufacturing process. Based on the above design and fabrication, an entire soft helical actuator was fabricated, and used as a gripper to handle slender objects.